2004
DOI: 10.1200/jco.2004.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transducer and Activator of Transcription-5 Activation and Breast Cancer Prognosis

Abstract: In our study, active Stat5 distinguishes breast cancer patients with favorable prognosis, and may be a useful marker for selection of more individualized treatment, especially in localized disease. These findings require confirmation in a large prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
168
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(187 citation statements)
references
References 22 publications
17
168
1
1
Order By: Relevance
“…The role of STAT5 transcription factor in breast tumorogenesis has been underlined in recent studies (29,30). STAT5 appeared to be constitutively phosphorylated in the three cell models expressing PrlR I146L .…”
Section: Discussionmentioning
confidence: 99%
“…The role of STAT5 transcription factor in breast tumorogenesis has been underlined in recent studies (29,30). STAT5 appeared to be constitutively phosphorylated in the three cell models expressing PrlR I146L .…”
Section: Discussionmentioning
confidence: 99%
“…Prl induced activation of JAK2 prevents breast cancer cells mesenchymal transition and acts as an invasion suppressor [44,45] . Reduced phosphorylation of STAT5 in breast cancer highlights patients with a worse prognosis of disease development [46] .…”
Section: Jak-stat Signaling and Carcinogenesismentioning
confidence: 99%
“…Wang et al concluded that women whose prolactin level fell postoperatively had significantly shorter overall survival compared with those who had a persistent elevation for 10 days (P \ 0.005). Furthermore, in a recent study, activated Stat5, a key prolactin-induced transcription factor [39], was significantly associated with better prognosis breast cancer [40]. Thus prolactin may have a role in reducing breast cancer incidence [41].…”
Section: Prolactinmentioning
confidence: 93%